Palm oil mill effluent : a waste or a raw material? - Salihu, Aliyu; Alam, Md. Zahangir (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2012)
Environmental issues are increasingly becoming more important globally. Large quantities of Palm oil mill effluent (POME) are generated annually during crude palm oil production. In this review, POME was considered as a biphasic product; being a major source of pollution in Malaysia due to its high organic load and as a cheap renewable residue which has been found to be useful in the production of fertilizers, citric acid, bioethanol, biohydrogen, bioplastic, hydrolytic enzymes, among others. Some of the benefits that can be derived from these productions include lower production cost, less waste and reduced energy consumption. Thus, recent advances in biotechnology could offer better solutionsto POME treatment by using it as a raw material to develop some valueadded products